Returns to tenure of seniority? - I. Sebastian Buhai; Miguel Portela; Coen N. Teulings; Aico van Vuuren (Institute for the Study of Labor (IZA), 2008)
This study documents two empirical regularities, using data for Denmark and Portugal. First, workers who are hired last, are the first to leave the firm (Last In, First Out; LIFO). Second, workers' wages rise with seniority (= a worker's tenure relative to the tenure of her colleagues). We seek to explain these regularities by developing a dynamic model of the firm with stochastic product demand and hiring cost (= irreversible specific investments). There is wage bargaining between a worker and its firm. Separations (quits or layoffs) obey the LIFO rule and bargaining is efficient (a zero surplus at the moment of separation). The LIFO rule provides a stronger bargaining position for senior workers, leading to a return to seniority in wages. Efficiency in hiring requires the workers' bargaining power to be in line with their share in the cost of specific investment. Then, the LIFO rule is a way to protect their property right on the specific investment. We consider the effects of Employment Protection Legislation and risk aversion.
Keywords: J31; 330; Irreversible investment; efficient bargaining; seniority; LIFO; matched employer-employee data; EPL; Betriebszugehörigkeit; Erwerbsverlauf; Lohn; Verhandlungstheorie; Arbeitnehmerschutz; Risikoaversion; Theorie; Dänemark; Portugal